Accretion processes in astrophysics - Shakura, N.; Kolesnikov, D. A.; Postnov, K. A.; Volkov, I. M.; Bikmaev, I. F.; Irsmambetova, T. R.; Staubert, R.; Wilms, Jörn; Irtuganov, E.; Shurygin, P.; Golysheva, P. Yu; Shugarov, S. Yu; et al. (Physics-Uspekhi, 2019)
Accretion onto magnetized neutron stars is considered using as a case study long-term X-ray and optical observations of HZ Her/Her X-1, an X-ray binary system with a 1.7-day orbital period where disc accretion occurs from the optical donor star (HZ Her) onto a neutron star (Her X-1). On top of orbital variability and pulsating X-ray emission from the neutron star rotating with a period of about one second, a 35-day X-ray modulation of emission is observed. The 35-day variability is due to a tilted precessing accretion disc that periodically screens X-ray emission from the neutron star. The disc precession that occurs in the direction opposite to the orbital motion is determined by the joint action of the tidal torque from the donor and dynamical torque from the gas streams. Several dozen thousand broadband UBV photometric observations of HZ Her have been obtained since 1972. The shape of the orbital light curves of HZ Her also changes with the 35-day cycle phase. The orbital variability can be reproduced in a model that includes a precessing tilted and warped accretion disc around a freely precessing neutron star. The disc is warped near its inner edge due to interaction with the rotating neutron star magnetosphere. The magnetic torque depends on the precessional phase of the neutron star. The X-ray emission flux from the neutron star also depends on the free precession phase that modulates the heating of the optical-star atmosphere and the intensity of gas streams. We show that this model reproduces well both optical observations of HZ Her and the behavior of the 35-day X-ray cycle.
CRIS-Team WoS Importer:2020-03-24